AN ANALYSIS OF PROBLEM BASED LEARNING IMPLEMENTATION IN SEVENTH GRADERS’ PRESENTATION SKILL AT SMP NEGERI 2 MANDREHE BARAT - Asnini Junita Zai; Yaredi Waruwu; Hidayati Daeli; Afore Tahir Harefa (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the implementation of the Problem-Based Learning (PBL) model in improving the presentation skills of seventh-grade students at SMP Negeri 2 Mandrehe Barat. This research employs a descriptive qualitative method involving one English teacher and thirty-six seventh-grade students. Data were collected through observation, interviews, and documentation. The findings show that the PBL model was implemented through five main stages: problem orientation, organizing students for problem analysis, guiding individual or group investigations, developing and presenting results, and reflecting on and evaluating the problem-solving process. Throughout the learning process, students actively participated in group discussions, identified real-world problems, and presented their ideas using descriptive text as the learning material. The results indicate that PBL effectively enhanced students’ presentation skills, as measured by seven key indicators: confidence, presentation structure, language use, intonation and articulation, audience interaction, use of visual aids, and time management. Improvements were evident in students’ confidence in public speaking, the clarity and structure of their material and presentation delivery, and their ability to manage presentation time efficiently. However, several obstacles were also identified, such as the teacher not fully implementing PBL procedures due to an incomplete teaching module. This study concludes that Problem Based Learning is a beneficial instructional model for developing students’ presentation skills.